Reconsidering the Terminology: Study Participants as “Subjects” or Not? - Corpuz, Jeff Clyde (Substance abuse : research and treatment, 2023)
The article highlights the importance of semantics in shaping our perception of this relationship and the ethical, psychological, and practical dimensions of conducting research on human beings. The term “subjects” implies passivity and contradicts the principles of informed consent and participant autonomy, whereas research physicians often maintain a similar patient-physician relationship with participants. The article suggests that adopting more appropriate terminology, such as “participants” or “volunteers,” can better acknowledge their active role and foster collaboration. The author emphasizes that language in scientific discourse plays a significant role in upholding ethical principles and preserving the unique physician-participant relationship in clinical research.